2022
DOI: 10.1038/s41419-022-04652-9
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MUC15 by miR-183-5p.1 promotes liver tumor-initiating cells properties and tumorigenesis via regulating c-MET/PI3K/AKT/SOX2 axis

Abstract: Mucin 15 (MUC15) is reportedly aberrant in human malignancies, including hepatocellular carcinoma (HCC). However, the role of MUC15 in the regulation of liver tumor-initiating cells (T-ICs) remains unknown. Here, we report that expression of MUC15 is downregulated in liver T-ICs, chemoresistance and recurrent HCC samples. Functional studies reveal that MUC15 inhibits hepatoma cells self-renewal, malignant proliferation, tumorigenicity, and chemoresistance. Mechanistically, MUC15 interacts with c-MET and subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…MUC15 inhibits hepatoma cell self-renewal, malignant proliferation, tumorigenicity, and chemoresistance by interacting with c-Met and subsequently inactivating the PI3K/AKT/SOX2 signaling pathway. The MUC15/c-Met/PI3K/AKT/SOX2 axis determines the responses of hepatoma cells to lenvatinib treatment, as supported by the observation that MUC15 overexpression abrogates lenvatinib resistance [ 160 ]. In addition, miR-552 promotes the proliferation and metastasis of cervical cancer cells by targeting the MUC15 pathway [ 161 ].…”
Section: Genes Associated With Lenvatinib Resistancementioning
confidence: 99%
“…MUC15 inhibits hepatoma cell self-renewal, malignant proliferation, tumorigenicity, and chemoresistance by interacting with c-Met and subsequently inactivating the PI3K/AKT/SOX2 signaling pathway. The MUC15/c-Met/PI3K/AKT/SOX2 axis determines the responses of hepatoma cells to lenvatinib treatment, as supported by the observation that MUC15 overexpression abrogates lenvatinib resistance [ 160 ]. In addition, miR-552 promotes the proliferation and metastasis of cervical cancer cells by targeting the MUC15 pathway [ 161 ].…”
Section: Genes Associated With Lenvatinib Resistancementioning
confidence: 99%
“…The response of carcinoma cells to lenvatinib is governed by the MUC15/c-MET/PI3K/AKT/SOX2 axis, and MUC15 overexpression can overcome lenvatinib resistance. 77 Takehara et al found in 2020 that long-term exposure to lenvatinib decreases the expression of fibroblast growth factor 19 (FGF19) in HCC cells but that re-expression of FGF19 can increase sensitivity to lenvatinib. ST6 Beta-Galactoside Alpha-2,6-Sialyltransferase 1 (ST6GAL1) is a tumor-derived secretory protein that is positively controlled by FGF19, according to proteomic and secretome studies.…”
Section: Regulation In Cell Signaling Pathwaysmentioning
confidence: 99%
“…Researchers discovered that miR-183-5p.1 specifically targets the 3'-UTR of the unique protein MUC15 in liver tumorinitiating cells (T-ICs) and that the MUC15/c-MET/PI3K/AKT/SOX2 axis controls the responses of hepatoma cells to lenvatinib treatment. 77 In lenvatinib-resistant cells, Sun et al demonstrated that miR-128-3p strongly inhibits the regulation of c-Met. Lenvatinib resistance is caused by miR-128-3p and c-Met, which control the progression of the ERK cell cycle and the AKT apoptotic pathway.…”
Section: Noncoding Rna Regulationmentioning
confidence: 99%
“…miR-125b-5p was upregulated in HCC with SOR, and the 50% inhibitory concentration (IC50) of SOR in HCC was signi cantly increased after overexpression of miR-25b-5p, indicating that miR-125b-5p can promote the HCC to SOR [10] . Not only that, miR-183-5p has been identi ed as a potential oncogene associated with various processes, including proliferation, apoptosis, and metastasis, especially resistance [11,12] . Recent studies indicate that elevated miR-183-5p expression levels correlate with poor survival in HCC patients [12] .…”
Section: Introductionmentioning
confidence: 99%